2015
DOI: 10.1088/0031-9155/60/10/3975
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of transcranial focusing thermal deposition in nonlinear HIFU brain surgery by numerical simulation

Abstract: As the skull induces strong aberrations in phase and amplitude during transcranial treatment of brain surgery, high-intensity focused ultrasound suffers degradation in beam shape and deposits significant heat in the skull which may cause thermal damage to the bone and surrounding tissue. The goal of this study is to optimize the transcranial pressure and thermal fields to reduce thermal damage to the skull and simultaneously concentrate more energy in the focal region and make its size controllable during tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 38 publications
0
27
0
Order By: Relevance
“…Based on the self-programming simulation, we have already accurately reproduced the tFUS propagation through the skull [ 24 , 25 ]. Throughout the paper, the nonlinear Westervelt equation is used to describe acoustic fields in the simulation [ 26 , 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…Based on the self-programming simulation, we have already accurately reproduced the tFUS propagation through the skull [ 24 , 25 ]. Throughout the paper, the nonlinear Westervelt equation is used to describe acoustic fields in the simulation [ 26 , 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…To accurately predict brain current flow produced during stimulation, one needs to specify the (1) relevant aspects of the stimulation device, and (2) relevant tissue properties; below we consider the relevant features each case. In this review, we focus on electrical stimulation, but in any form of energy application where the physics are well defined, then defining device and tissue properties should lead to straightforward prediction of energy dissipation in the body (Cho et al, 2010;Deng et al, 2014;Ding et al, 2015;Jagdeo et al, 2012;Lee et al, 2015;Wu et al, 2012).…”
Section: Step 1: Forward Models Of Current Flowmentioning
confidence: 99%
“…Based on the time reversal (TR) method ( Ding et al, 2015 ), place the pulse wave virtual point sound source S 0 ( t ) at the target focus F, as shown in Figure 2 ,…”
Section: Models and Methodsmentioning
confidence: 99%
“…In mouse or rat animal experiments, because the mouse skull is very thin, it has little effect on the ultrasound transcranial focused sound pressure field, whereas the human skull is approximately 2.33–19.08 mm thick and has heterogeneity, which will distort the ultrasound transcranial focused sound pressure field. Unfavorable phenomena such as phase distortion and defocusing occur, which cause distortion of the focus position and the shape of the TMAS induced current ( Ding et al, 2015 ). In 2006, Yand et al recorded the frequency of EEG in adult mice at 24–42°C for 60 min, and found that brain tissue damage is reversible when the temperature is less than 40°C ( Yang and Qi, 2006 ).…”
Section: Introductionmentioning
confidence: 99%